APPLICATION OF SELF-REGULATION IN PIANO LEARNING (Proceedings of the International Conference on Education, 2022)
Self-regulated learning is a process in which the learner may create suitable learning goals and drive himself or herself, with or without the assistance of the teacher, to actively apply learning techniques and attain the learning objectives. It is not only an active involvement process, but also a long-term and consistent capacity. This study integrates self-regulation learning theory with piano learning, expounds on the significance of self-regulation learning capacity in piano learning, and suggests a training strategy. According to the self-regulation learning theory, the psychological mechanism of piano learning self-regulation is investigated, and a plan for cultivating students' piano self-regulation learning ability is proposed based on four aspects of students' cognition, motivation, behavior, and learning situation, and piano students from 16 music schools are chosen. An 8-week experiment was conducted. Innovatively integrates the feedback form of self-regulated learning into piano learning, and establishes a scoring standard according to the international piano performance evaluation rules. Independent T-test analysis was performed on the obtained results. The result is remarkable. It is expected that the training program of self-regulation learning ability in piano learning improves students' piano learning performance better than the ordinary piano learning mode. This research can improve the efficiency of piano learning and contribute to the promotion of piano education.
Keywords: piano learning; self-regulated learning; music; performance eeducation